Educational game in teaching data structure: combining Education 5.0, gamification and storytelling - Barbosa, Huminig Schmiedt; Silva, Felippe Fernandes da; Campano Junior, Maurilio Martins; Aylon, Linnyer Beatrys Ruiz (Companion Proceedings of the Brazilian Symposium on Computer Games and Digital Entertainment (SBGames); 2023: Companion Proceedings of the 22nd Brazilian Symposium on Games and Digital Entertainment, 2023)
New teaching approaches are being increasingly applied in schools and universities. In this regard, technology plays a fundamental role, serving as a facilitator of education. Associated with technology, educational games are adapting more and more to classroom use, utilizing genres like storytelling to explain theoretical concepts. Thus, the objective of this work is to present a game prototype that utilizes elements of Education 5.0, gamification, and story-telling in the teaching of data structures. The prototype was evaluated in the classroom and obtained positive results in terms of student acceptance.